PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIFE STAD UNTUK MENINGKATKAN HASIL BELAJAR PAI SISWA DI SMP NEGERI 19 BENGKULU SELATAN - Ririn Selvianti (Jurnal Pendidikan, 2023)
This research aims to implementing cooperative leraning model tife STAD to improve student’s Islamic religious education learning outcome. This research is conducted at SMP Negeri 19 Bengkulu Selatan grade VII with classroom action research method through cycle model (total three cycles). In each cycle continuously carried out planning, acting, observing and reflecting. The results showed that: 1) in first cycle student achievement increased from average score of 63,08 to 71,86 with the lowest score of 60 and the highest score 85 of which 17 students scored below the KKM average and 9 students scored above KKM average; 2) in the second cycle, student achievement increased from an average score of 71.86 to 75.19 with the lowest score of 65 and the highest score of 88 of which 11 students scored below the KKM average and 15 students scored above the KKM average . So if it is calculated based on the percentage of learning completeness it has increased from 34.61% to 57.70% while students who are still below the KKM average are from 65.39% to 42.30%; 3) student achievement increased from an average score of 75.19 to 79.15 with the lowest score of 65 and the highest score of 95 of which 4 students scored below the KKM average and 22 students scored above the KKM average. So if it is calculated based on the percentage of learning completeness it has increased from 57.70% to 84.61% while students who are still below the KKM average are from 42.3% to 15.39%.